Identification of glucocorticoid receptors as potential modulators of parasympathetic and sympathetic neurons within rat intracardiac ganglia - Mousa, Shaaban A.; Dehe, Lukas; Aboryag, Noureddin; Shaqura, Mohammed; Beyer, Antje; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Neuroanatomy, 2022)
Evidence indicates that glucocorticoid receptors (GR) play a regulatory role in cardiac function, particularly with regard to the autonomic nervous system. However, the precise distribution of GR in relation to the parasympathetic and sympathetic innervations of the heart is yet unknown. The present study used tissue samples from rat heart atria to perform conventional reverse-transcriptase polymerase chain reaction (PCR), Western blot, and double immunofluorescence confocal analysis of GR with the neuronal markers vesicular acetylcholine transporter (VAChT), tyrosine hydroxylase (TH), and calcitonin gene-related peptide (CGRP). Double immunofluorescence labelling revealed that GR were co-expressed with VAChT in large diameter parasympathetic principal neurons as well as on nerve terminals innervating atrium. Also, GR colocalized with the sympathetic neuronal marker TH in a cluster of small intensely fluorescent (SIF) cells, on intracardiac nerve terminals as well as in the atrial myocardium. Intriguingly, approximately 20% of GR immunoreactive neurons co-localized with MR. GR immunoreactivity was scarcely identified on CGRP-IR sensory nerve terminals. Finally, PCR and Western blot confirmed the presence of GR and MR in rat heart atria. This study provides evidence for the existence of GR predominantly on cardiac parasympathetic neurons and TH-immunoreactive SIF cells as well as neurons suggesting a functional role of cardiac GR on cardiovascular function by modulation of the cardiac autonomic nervous system.